Fiscal Consolidation and Climate Policy: An Overlapping Generations Perspective - Sebastian Rausch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We examine the distributional and e ciency impacts of climate policy in the context of fiscal consolidation in a dynamic general-equilibrium overlapping generations model of the US economy. The model includes a disaggregated production structure, including energy sector detail and advanced low- or zero-carbon energy technologies, and detail on government taxes and spending. In contrast to revenue-neutral carbon tax swaps, using the carbon revenue for deficit reduction implies a relaxation of future public budgets as debt repayment results in lower interest obligations. While we show that the intergenerational welfare impacts depend importantly on what tax recycling instrument is used, we find that combining debt consolidation with a carbon policy entails the possibility of sustained welfare gains for future generations. We thus argue that combining fiscal and climate policy may o er the chance for positive societal gains (without considering potential benefits from averted climate change). Importantly, this may enhance the political support for revenue-raising climate policies that are framed over the next couples of decades.
Keywords: Q54; C68; H60; 330